Self Efficacy and Family Support in Elderly Hypertension Anxiety: Self Efficacy dan Dukungan Keluarga pada Kecemasan Lansia Hipertensi - Dela Istiqomah; Edy Soesanto; Sri Karyati (Academia Open, 2026)
Abstract General Background: Hypertension in older adults is frequently accompanied by anxiety that may interfere with daily functioning and chronic disease management. Specific Background: Elderly patients with hypertension often experience psychological distress related to long-term treatment and risk of complications, while self efficacy and family support are considered important psychosocial factors in coping with illness. Knowledge Gap: Previous findings regarding the association between self efficacy and anxiety are inconsistent, and limited studies analyze self efficacy and family support simultaneously in primary health care settings. Aims: This study examined the relationship between self efficacy and family support with anxiety levels among elderly hypertensive patients in the Kragan II Community Health Center area. Results: Using a cross sectional correlational design with 98 respondents and Spearman Rank analysis, significant negative correlations were found between self efficacy and anxiety (p < 0.001; r = -0.580) and between family support and anxiety (p < 0.001; r = -0.370). Novelty: This study integrates two psychosocial variables within one analytical framework in a primary care context. Implications: The findings provide a basis for family-based nursing strategies, including hypertension self management education and structured family involvement to address anxiety among elderly patients. Highlights • Majority of participants experienced moderate anxiety despite high perceived personal capability.• Insufficient household assistance was reported by nearly half of respondents.• Significant inverse correlation identified through Spearman Rank statistical testing. Keywords Self Efficacy; Family Support; Anxiety Level; Elderly Hypertension; Primary Health Care